Davutoğlu Doctrine and Turkish Foreign Policy in the Middle East: A Critical Constructivist Analysis - Miranto, Edi (JPP (Jurnal Politik Profetik), 2017)
Referring to the argument that a state’s historic background and geographic location inthe world are inherent elements of its foreign policy narrative which constitutes its identity,this article examined and brought narratives on the reconstruction of Turkish foreignpolicy towards the Middle East which was directed by a foreign policy doctrine ofDavutoğlu as defined Davutoğlu Doctrine. Using a critical constructivist perspective, itcontends that Davutoğlu’s foreign policy vision for Turkey is an attempt to reconstructthe international role and responsibilities of Turkey through a transformed identitybased on a reinterpretation of its historical heritage and geographic location. This articleconcluded that the Davutoğlu Doctrine’s vision was not only an endeavor to overturnthe traditional tendencies in Turkish foreign policy, but also in any ways, is a task ofidentity transformation. Further, this new activism has led to a shift in the axis of itsforeign policy from the Western orientation to a more assertive, strict independent foreignpolicy that is central to the Davutoğlu Doctrine. Finally, Davutoglu Doctrine canbe recognized that it has reconstructed Turkey’s state identity to reshape Turkish foreignpolicy onwards to the Middle East aiming to reposition Turkey as the global representativeand a key player in the region.